Young People's Perspectives on the Value and Meaning of Art during the Pandemic. (September 2022) - Rizzo, Sara; Knox, Ellie; Azizi, Naqi; Sulevani, Isra; Chia, Charmaine; Leo, Marie; Spina, Micol; Percy-Smith, Barry; Tay, Chermaine; Monchuk, Leanne; Day, Laurie
This contribution draws on the voices and reflections from young people as co-researchers in the Growing-Up Under Covid-19 project – a longitudinal ethnographic action research project to document, share, and respond to impacts of the pandemic on different spheres of young people's lives. The research was conducted entirely online over 18 months in seven countries and has involved youth-led approaches to research, including video diaries and the use of artefacts and visual material to convey their experiences and support reflection and dialogue across research groups and with external stakeholders. In this contribution, the young co-researchers reflect on their rationale for using different visual media and why this was important for them. They also reflect on the significance of the representations in the visual images and how these images communicate how young people's understanding of COVID and its impact on young people has changed (or given new meaning to) and how this in turn has given rise to particular responses and opportunities for young people. The article draws on examples of different visual forms selected by young people in Singapore, Italy, Lebanon, and the UK nations, including video, drawing, photography, and crafts. These different media and links to videos were included in the accompanying document. The contribution explores the different narratives and meanings behind the visuals, using the words of young people themselves, interspersed with narration from the adult researchers.